(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents an in-depth analysis of the scientific and theoretical foundations of innovative methods in the development of STEAM education (Science, Technology, Engineering, Arts, Mathematics) in higher pedagogical education. It explores the conceptual and theoretical bases of STEAM, the application of modern teaching methods in the educational process, and the conditions necessary for their effective implementation. The study also examines national and international experiences in fostering creativity, critical thinking, and practical skills among students through innovative approaches. The research findings confirm that STEAM education significantly enhances student engagement and competency development in pedagogical contexts.